2004
DOI: 10.1117/1.1781665
|View full text |Cite
|
Sign up to set email alerts
|

Real-time joint transform correlator using compressed reference images

Abstract: A real-time implementation of a joint transform correlator by using JPEG-compressed reference images is proposed in order to solve storage problems and improve the time response of automatic target recognition systems. The correlation performance is studied quantitatively by using two types of images with different spatial-frequency contents. The simulation results show that in comparison with the compressed high-spatial-frequency images, the joint transform correlator using the compressed low-spatial-frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…High spatial-frequency losses caused by the compressions with the QF¼10 and 40 are not significantly different. This is in agreement with our previous studies which found that the JPEG-compression effect on the low-contrast pattern recognitions is not significant [31].…”
Section: Recognition In the Presence Of Weak Noisesupporting
confidence: 95%
“…High spatial-frequency losses caused by the compressions with the QF¼10 and 40 are not significantly different. This is in agreement with our previous studies which found that the JPEG-compression effect on the low-contrast pattern recognitions is not significant [31].…”
Section: Recognition In the Presence Of Weak Noisesupporting
confidence: 95%
“…c T stands for the contrast ratio of the target to the reference images which becomes greater, equal, or smaller than 1 when the contrast of the reference image is lower, equal, or higher than that of the target, respectively. After an optical Fourier transformation by the lens L, the joint Fourier spectra is captured by the camera CCD 2 placed at the rear focal plane of the lens L. The captured JPS can be mathematically expressed as (5) where are the spatial frequency coordinates in the horizontal and the vertical directions at the Fou rier plane, respectively. Multiplication of the recorded JPS and the wavelet filter gives…”
Section: Wavelet Based Joint Transform Correlationmentioning
confidence: 99%
“…In real time JTC [3][4][5][6], a target image captured by a CCD sensor and a reference image stored in a computer system are displayed side by side onto an electrically addressed SLM (EASLM) placed in a front focal plane of a Fourier transforming lens. By illuminating the EASLM with a coherent collimated beam, the displayed joint images are optically Fourier transformed by the lens.…”
Section: Introductionmentioning
confidence: 99%